FORMATION OF MORAL AND MORAL EDUCATION OF FUTURE PHYSICAL EDUCATION AND SPORTS TEACHERS - Jumaboyev Muhammadjon Alisher ugli (Journal of new century innovations, 2022)
This article considers the role of physical education in circle classes to the spiritual upbringing of the students in Higher Educational institutions.